Faktor Risiko Kejadian Keracunan Pestisida Organofosfat pada Petani Hortikultura di Kecamatan Ngablak Kabupaten Magelang, 2008 - Asror, Farikhun; Sulistiyani, Sulistiyani; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background: Pesticides spraying which is not follow the regulation, will give many effect on  human health. Many adverse  effects on human health include anemia, neurodegenerative diseass, endocrine disruption caused by chronic  poisoning of pesticides  on farmers. Pesticides poisoning   can be detected  by the examination of the blood cholinesterase activities. Factors  that influence to the occurrence of pesticides poisoning are the factors from the inside of the human body             ( internal) and outside of the human body ( external) The objective of this research was determined risk factors of organophosphate pesticides poisoning on the horticultura sprayer farmers in agriculture area of Tejosari village,  Ngablak Sub- distric , Magelang. Method: This research used case control design study, with 100 samples included of cases 50 and controles 50. The population was sprayer farmers and sprayer farmer labour of  horticultura agriculture area of Tejosari. Data  was analyzed by univariate analysis by using table of frequency distribution and analyze the percentage, bivariate analysis by using statistical test of Chi-square and multivariate analysis by using statistical test of logistic regretion. Result: Total respondens base on group of age mostly 35 – 44 ages (31%), respondens level  of education which graduated from elementary school (76%). From multivariate analisis showed that risk factors for pesticides poisoning were less knowledge (p = 0,041; OR: 3,630; 95% C.I : 1,057–12,529); abnormal nutrition status (p = 0,048;  OR: 6,623; 95% C.I. : 1.015–43.204); anemia (p = 0,009; OR : 5,987; 95% C.I. : 1,564-22,914); using of personal protective equipment not complete (p=0,001 OR : 26,661; 95% CI : 5,841-121,705) and over dose pesticide (p = 0,003; OR 8,095; 95% C.I. 2,055-31,883). Conclusion : using of personal protective equipment complete was the most influence risk factor to the occurrence of organophosphat pesticide poisoned at the horticultura sprayer farmers of plant pest. It is suggested that the sprayer farmers have to use complete personal protective equipment each time used pesticides. Key Words : Risk factor, Cholinesterase activities, Organophosphat the pesticide poisoning